A method for manufacturing an all-solid-state battery with a stable interface of a lithium anode

By using a sulfide-based solid electrolyte layer and a lithium metal laminate in lithium secondary batteries and emitting ultrasonic waves or sound waves to the laminate, the reaction problems of lithium metal and liquid electrolyte and the interface inhomogeneity are solved, and high efficiency is achieved , durable all-solid-state battery.

CN111293350BActive Publication Date: 2025-02-14HYUNDAI MOTOR CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201910379620.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-10
Filing Date
2019-05-08
Publication Date
2025-02-14
Estimated Expiration
2039-05-08

AI Technical Summary

Technical Problem

The violent reaction between lithium metal and liquid electrolyte in lithium secondary batteries makes it difficult to use lithium metal as an anode, and the interface between lithium metal and solid electrolyte layer is uneven, increasing resistance and reducing the durability and efficiency of the battery.

Method used

By preparing a solid electrolyte layer including a sulfide-based solid electrolyte, lithium metal is provided to prepare the superposition and emit ultrasonic waves or sound waves to the superposition to form a uniform interface.

Benefits of technology

A uniform interface is achieved between the lithium metal and the solid electrolyte layer, reducing resistance, improving the durability and efficiency of the battery, and lithium metal can be used as the anode of the all-solid state battery, increasing the energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111293350B_ABST
    Figure CN111293350B_ABST
Patent Text Reader

Abstract

A method for manufacturing an all-solid-state battery having a stable interface with a lithium anode, the method comprising preparing a solid electrolyte layer, placing lithium metal on the solid electrolyte layer to prepare a laminate, and emitting ultrasonic or acoustic waves to the laminate. The method provides an all-solid-state battery having a stable interface between an anode formed of lithium metal and a solid electrolyte layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing an all-solid-state battery having a stable interface between an anode formed of lithium metal and a solid electrolyte layer. Background Art

[0002] Among metal elements, lithium is an element with the lowest oxidation-reduction potential of -3 V. Therefore, when lithium metal is used as an anode of a lithium secondary battery, a capacity per unit weight of about 3,860 mAh / g and a capacity per unit weight of about 2,060 mAh / cm can be achieved. 3 The capacity per unit volume can therefore provide a lithium secondary battery with excellent energy density.

[0003] However, lithium metal reacts violently with the liquid electrolyte of lithium secondary batteries, and therefore, it is difficult to use lithium metal as the anode of lithium secondary batteries.

[0004] Korean Patent Application No. 10-1900823 and Korean Patent Laid-Open Publication No. 10-2018-0104173 disclose all-solid-state batteries. Summary of the invention

[0005] One aspect of the present invention provides a method for manufacturing an all-solid-state battery that can form a stable interface between an anode formed of lithium metal and a solid electrolyte layer to minimize chemical reactions therebetween.

[0006] Another aspect of the present invention provides a method for manufacturing an all-solid-state battery, the method comprising preparing a solid electrolyte layer, providing lithium metal to the solid electrolyte layer to prepare a stack, and emitting ultrasonic waves or sound waves to the stack.

[0007] In one embodiment, the solid electrolyte layer may include a sulfide-based solid electrolyte.

[0008] In another embodiment, the method may further include providing a cathode to one surface of the solid electrolyte layer before providing the lithium metal.

[0009] In another embodiment, when the cathode is provided, the cathode and the solid electrolyte layer may be stacked and then pressurized.

[0010] In another embodiment, the lithium metal may be lithium foil.

[0011] In another embodiment, when emitting ultrasonic waves or sound waves to the stack, an ultrasonic generator or sound wave generator may be disposed outside the stack and directly emit ultrasonic waves or sound waves to the stack without sealing or covering the stack with a separate substrate.

[0012] In another embodiment, the ultrasonic generator or sound wave generator may be disposed on the entire or certain areas of the outer surface of the laminate.

[0013] In another embodiment, while emitting ultrasonic or sonic waves to the stack, the stack may be inserted into a soft bag, and then the ultrasonic or sonic waves may be emitted to the stack.

[0014] In another embodiment, the laminate is inserted into a soft bag while emitting ultrasonic or sonic waves to the laminate, so that the entirety or some areas of the outer surface of the laminate are in contact with the inner surface of the soft bag.

[0015] In another embodiment, when emitting ultrasonic waves or sound waves to the stack, an ultrasonic generator or a sound wave generator may be disposed outside the soft-pack bag and emit ultrasonic waves or sound waves to the stack.

[0016] In another embodiment, the ultrasonic generator or sound wave generator may be disposed on the entire or certain areas of the outer surface of the soft bag.

[0017] In another embodiment, when the ultrasonic wave or the sound wave is radiated to the laminate, the ultrasonic wave or the sound wave having a frequency of 20 kHz to 40 kHz may be radiated to the laminate for 1 to 10 minutes.

[0018] In another embodiment, emitting ultrasound or sound waves to the stack may include emitting ultrasound or sound waves to the stack for 10 to 30 seconds, and then pausing the emission of ultrasound or sound waves to the stack for 10 to 30 seconds. The emitting ultrasound or sound waves to the stack and pausing the emission of ultrasound or sound waves to the stack may be repeated 5 to 10 times.

[0019] In another embodiment, when the ultrasonic wave or the sound wave is radiated to the laminate, the ultrasonic wave or the sound wave may be radiated to the laminate while pressurizing the laminate in the thickness direction of the laminate at a pressure of 10 MPa to 200 MPa.

[0020] In another embodiment, when emitting the ultrasonic wave or the sonic wave to the laminate, the ultrasonic wave or the sonic wave may be emitting to the laminate while maintaining the laminate at a temperature of 25°C to 100°C.

[0021] In another embodiment, the method may further include pressurizing the laminate in a thickness direction of the laminate at a pressure of 10 MPa to 200 MPa while maintaining the laminate at a temperature of 25° C. to 100° C. after emitting ultrasonic waves or sound waves to the laminate.

[0022] Another aspect of the present invention provides a method for manufacturing an all-solid-state battery, the method comprising: providing a solid electrolyte layer having a cathode attached to a surface of the solid electrolyte; placing a lithium metal foil on another surface of the solid electrolyte layer to prepare a laminate; and applying ultrasonic waves to the laminate. In one embodiment, the laminate is wrapped in a soft bag and ultrasonic waves are applied to the soft bag.

[0023] Other aspects and embodiments of the invention are discussed below.

[0024] The above features and other features of the present invention are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and other features of the present invention will be described in detail below with reference to the embodiments of the attached drawings, which are given below only for illustration purposes and are therefore non-limiting to the present invention, wherein:

[0026] Figure 1 A flowchart schematically illustrating a method for manufacturing an all-solid-state battery according to one embodiment of the present invention;

[0027] Figure 2 A cross-sectional view schematically illustrating a stack according to one embodiment of the present invention;

[0028] Figure 3 A cross-sectional view schematically illustrating one type of inserting a stack into a soft bag;

[0029] Figure 4 A cross-sectional view schematically illustrating another type of inserting a stack into a soft bag;

[0030] Figure 5 Reference figures for explaining a method of emitting ultrasonic or sound waves to a laminate;

[0031] Figure 6 A flowchart schematically illustrating a method for manufacturing an all-solid-state battery according to another embodiment of the present invention;

[0032] Fig. 7A A photograph showing a scanning electron microscope (SEM) analysis result of a stack of an all-solid-state battery according to an embodiment, Figure 7B is a magnified photograph showing the interface between lithium metal and the solid electrolyte layer;

[0033] Fig. 8A is a photograph showing the SEM analysis result of the laminate of the all-solid-state battery according to Comparative Example 1, Figure 8B is a magnified photograph showing the interface between lithium metal and the solid electrolyte layer;

[0034] Fig.9A is a photograph showing the SEM analysis result of the laminate of the all-solid-state battery according to Comparative Example 2, Fig. 9B is a magnified photograph showing the interface between lithium metal and the solid electrolyte layer.

[0035] It should be understood that the accompanying drawings are not drawn to scale, but rather show slightly simplified depictions of various features illustrating the basic principles of the present invention. The specific design features of the present invention disclosed herein (including, for example, specific dimensions, directions, locations, and shapes) will be determined in part by the specific intended application and use environment.

[0036] In the figures, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures of the drawing. DETAILED DESCRIPTION

[0037] Reference will be made in detail to various embodiments of the present invention, examples of which are shown in the accompanying drawings and described below. Although the present invention is described in conjunction with the embodiments, it should be understood that this specification is not intended to limit the present invention to the embodiments. On the contrary, the present invention is intended to cover not only the embodiments, but also various substitutions, modifications, equivalents and other embodiments within the spirit and scope of the present invention as defined by the appended claims.

[0038] In the following description of the embodiment, terms such as "including", "having", etc. will be interpreted as indicating the presence of features, numbers, steps, operations, elements or parts described in the description, or a combination thereof, and do not exclude the presence of one or more other features, numbers, steps, operations, elements, parts, or a combination thereof, or the possibility of adding them. In addition, it should be understood that when a part (such as a layer, film, region, or substrate) is referred to as being "on" another part, the part can be "directly located on the other part" or the other part can be placed between the two parts. In the same way, it should be understood that when a part (such as a layer, film, region, or substrate) is referred to as being "under" another part, the part can be "directly located under the other part" or the other part can be placed between the two parts.

[0039] All numbers, values ​​and / or expressions representing the amount of components, reaction conditions, polymer compositions and mixtures used in this specification are approximate values, which reflect the measurement uncertainty generated when obtaining these values ​​from essentially different things, and unless otherwise stated, it should be understood that they are all modified by the term "about". In addition, it should be understood that if a numerical range is disclosed in the specification, unless otherwise stated, the range includes all continuous values ​​from the minimum value to the maximum value. Moreover, if such a range involves integers, unless otherwise stated, the range includes all integers from the minimum integer to the maximum integer.

[0040] All-solid-state batteries that use solid electrolytes instead of liquid electrolytes (electrolyte solutions) basically do not cause reactions between the electrolyte solution and lithium metal, so lithium metal is very likely to be used as the anode of all-solid-state batteries.

[0041] Moreover, in an all-solid-state battery, a solid electrolyte layer is formed, and lithium metal having high ductility can be easily attached to the electrolyte layer by simply applying pressure thereto.

[0042] However, it is extremely difficult for lithium metal to be uniformly bonded to the solid electrolyte layer. If the interface between lithium metal and the solid electrolyte layer is not uniform, the resistance will increase, making it difficult to drive the all-solid-state battery, and dendrites will form during charging and discharging, greatly reducing durability and efficiency.

[0043] Vacuum thermal deposition of lithium metal on one surface of a solid electrolyte layer can be used. However, such deposition methods may not be suitable for the manufacture of large-area all-solid-state batteries. Moreover, the surface of the deposited lithium metal is not uniform, so the charging and discharging efficiency may be reduced.

[0044] A method of combining lithium metal with one surface of a solid electrolyte layer and then heating and pressurizing the solid electrolyte layer provided with lithium metal can be used. However, such a heating and pressurizing method is suitable for the case where the solid electrolyte layer is an oxide-based solid electrolyte. Sulfide-based solid electrolytes have poor mechanical rigidity and are harmful to chemical reactions. Therefore, if lithium metal is attached to a solid electrolyte layer including a sulfide-based solid electrolyte by a heating and pressurizing method, a side reaction layer with high resistance can be formed by a chemical reaction between the two components. Moreover, if a large-area all-solid-state battery is manufactured, it is difficult to transfer heat and pressure evenly.

[0045] Figure 1 A flowchart schematically illustrating a method for manufacturing an all-solid-state battery according to an embodiment of the present invention. Referring to the figure, in an embodiment, the all-solid-state battery manufacturing method includes preparing a solid electrolyte layer (operation S10), attaching a cathode to one surface of the solid electrolyte layer (operation S20), preparing a stack by attaching lithium metal to the solid electrolyte layer (operation S30), and emitting ultrasonic waves or sound waves to the stack (operation S40).

[0046] When preparing the solid electrolyte layer (operation S10), the solid electrolyte layer may include a sulfide-based solid electrolyte. The sulfide solid electrolyte may be Li 2 SP 2 S 5 , Li 2 SP 2 S5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (m and n are positive numbers, Z is selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (x and y are positive numbers, M is selected from P, Si, Ge, B, Al, Ga and In) or Li 10 G 2 S 12 .

[0047] The solid electrolyte layer may be prepared by a wet method or a dry method.

[0048] The process of preparing the solid electrolyte layer by a wet method will be described below. In one embodiment, a slurry is prepared by dispersing a sulfide-based solid electrolyte in a solvent. The solid electrolyte layer is obtained by applying the slurry to a substrate at a specified thickness and then drying the slurry.

[0049] The process of preparing the solid electrolyte layer by a dry method will be described below. In one embodiment, the solid electrolyte layer is obtained by placing a powder of a sulfide-based solid electrolyte into a mold having a specified shape and size and then pressurizing the powder at a specified pressure.

[0050] However, the method of preparing the solid electrolyte layer is not limited thereto, and the solid electrolyte layer may be prepared by any method that allows the solid electrolyte layer to maintain its thickness, shape, etc.

[0051] If necessary, the solid electrolyte layer may further include a binder, and the specific type and content of the binder are not limited.

[0052] When providing the cathode (operation S20), the cathode may be placed on one surface of the solid electrolyte layer, followed by pressurization.

[0053] The cathode may include a cathode active material, a conductive material, and a solid electrolyte.

[0054] The specific type of the cathode active material is not limited. For example, the cathode active material may be an oxide active material or a sulfide active material.

[0055] The oxide active material may be a rock salt layer type active material (e.g. LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 or Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ), spinel active materials (such as LiMn 2 O 4 Or Li(Ni 0.5 Mn 1.5 ) 4 ), inverse spinel active materials (such as LiNiVO 4 or LiCoVO 4 ), olivine-type active materials (such as LiFePO 4 、LiMnPO 4 、LiCoPO 4 or LiNiPO 4) Silicon-containing active materials (e.g., Li 2 FeSiO 4 or Li 2 MnSiO 4 ), rock salt layer-type active materials in which a part of the transition metal is replaced by different kinds of metals (e.g., LiNi 0.8 Co (0.2-x) Al x O 2 (0 < x < 0.2)), spinel-type active materials in which a part of the transition metal is replaced by different kinds of metals (e.g., Li 1+x Mn 2-x-y M y O 4 (M is at least one selected from Al, Mg, Co, Fe, Ni, and Zn, and 0 < x + y < 2)) and lithium titanate (e.g., Li 4 Ti 5 O 12 ).

[0056] The sulfide active material may be Chevrel copper, iron sulfide, cobalt sulfide, or nickel sulfide.

[0057] The conductive material forms an electron conduction path in the cathode. The conductive material may be SP 2 carbon materials such as carbon black, conductive graphite, ethylene black, or carbon nanotubes or graphene.

[0058] The solid electrolyte may be the same as or different from the above-mentioned sulfide-based solid electrolyte included in the solid electrolyte layer. For example, the solid electrolyte may be Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiI, Li 2 S-P 2 S 5 -LiCl, Li 2 S-P 2 S 5 -LiBr, Li 2 S-P 2 S 5 -Li 2 O, Li 2 S-P 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (m and n are positive numbers, Z is selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (x and y are positive numbers, M is selected from P, Si, Ge, B, Al, Ga and In) or Li 10 G 2 S 12 .

[0059] The cathode can be prepared by a wet process or a dry process.

[0060] The process of preparing the cathode by a wet method will be described below. In one embodiment, a slurry is obtained by dispersing a cathode active material, a conductive material, and a solid electrolyte in a solvent. The cathode is obtained by applying the slurry to a substrate with a specified thickness and then drying the slurry. Here, a cathode current collector can be used as a substrate.

[0061] The process of preparing the cathode by a dry method will be described below. In one embodiment, the cathode is obtained by placing a cathode active material, a conductive material, and a solid electrolyte into a mold having a specified shape and size, and then pressurizing it at a specified pressure.

[0062] However, the method of preparing the cathode is not limited thereto, and the cathode may be prepared by any method that can allow the cathode to maintain its thickness, shape, etc.

[0063] The cathode may be formed to have the same area as the solid electrolyte layer or to have a smaller area than the solid electrolyte layer.

[0064] After the cathode is disposed on one surface of the solid electrolyte layer, the cathode and the solid electrolyte layer are pressurized at a specified pressure for a specified time to be densified. Here, the cathode may include a cathode current collector attached thereto.

[0065] When the stack is prepared by disposing lithium metal on the solid electrolyte layer (operation S30), the lithium metal is disposed on the other surface of the solid electrolyte layer so that the solid electrolyte layer is located between the cathode and the lithium metal.

[0066] Figure 2 1 is a cross-sectional view schematically illustrating a stacked structure. Referring to this figure, the stacked structure includes a solid electrolyte layer 10 , a cathode 20 provided on one surface of the solid electrolyte layer 10 , and a lithium metal 30 provided on the other surface of the solid electrolyte layer 10 .

[0067] The lithium metal 30 may be a lithium foil, and the specific thickness of the lithium metal 30 is not limited.

[0068] When emitting ultrasonic waves or sound waves to the stack (operation S40), energy is transmitted to the lithium metal and the solid electrolyte layer through the ultrasonic waves or sound waves, so that the floating interface between the lithium metal and the solid electrolyte layer formed when preparing the stack (operation S30) vibrates. Therefore, the uneven portion of the floating interface is aligned, thereby forming a flat interface between the lithium metal and the solid electrolyte layer.

[0069] Here, when the fluidity of the lithium metal is improved by controlling the frequency, emission time, temperature and pressure of ultrasonic or sound waves, a more excellent interface can be formed. The above conditions will be described later.

[0070] When emitting ultrasound or sound waves to the stack (operation S40), the ultrasound or sound waves may be emitted directly to the stack without sealing or covering the stack with a separate substrate, or may be emitted to the stack while inserting the stack into a soft pack bag. Figure 3 and Figure 4 It is a cross-sectional view schematically illustrating the insertion of the stack into the soft bag.

[0071] If ultrasonic waves or sound waves are directly emitted to the laminate, an ultrasonic generator or a sound wave generator may be disposed outside the laminate to emit ultrasonic waves or sound waves to the laminate.

[0072] If ultrasonic waves or sound waves are emitted to the stack under the condition that the stack is inserted into a soft bag, such as Figure 3 The entire outer surface of the laminate may be in contact with the inner surface of the soft bag as shown, or Figure 4 As shown, only certain areas of the outer surface of the laminate can be in contact with the inner surface of the soft bag. Figure 3 With a soft bag, energy can be more easily transmitted to the stack via ultrasound or sound waves.

[0073] Figure 5 A reference diagram for explaining a method of emitting ultrasonic waves or sound waves to a laminate. Referring to this figure, an ultrasonic generator or sound wave generator 50 may be disposed outside the soft package bag 40 to emit ultrasonic waves or sound waves A to the laminate.

[0074] The ultrasonic generator or sound wave generator 50 may be arranged to be in contact with the soft bag, or to be arranged to be spaced apart from the soft bag at a sufficient distance so as to transmit ultrasonic waves or sound waves to the soft bag.

[0075] Moreover, the ultrasonic generator or sound wave generator 50 can be arranged on the entire or certain areas of the outer surface of the soft package bag.

[0076] In order to transmit the ultrasonic wave or sound wave A to the laminate in an all-round manner, the ultrasonic wave generator or sound wave generator 50 can be configured to be in contact with the entire outer surface of the soft package bag 40 to generate ultrasonic waves or sound waves.

[0077] When the ultrasonic wave or the sound wave is emitted to the stack (operation S40), the ultrasonic wave or the sound wave having a frequency of 20 kHz to 40 kHz may be emitted to the stack for 1 minute to 10 minutes.

[0078] In more detail, when emitting ultrasound or sound waves to the stack (operation S40), emitting ultrasound or sound waves having a frequency of 20 kHz to 40 kHz to the stack for 10 to 30 seconds and then pausing the emission of ultrasound or sound waves to the stack for 10 to 30 seconds can be repeated 5 to 10 times.

[0079] If the emission of ultrasonic or sound waves to the stack is not suspended, the temperature of the stack may be excessively increased, and thus a uniform interface may not be formed between the lithium metal and the solid electrolyte layer.

[0080] In one embodiment of the present invention, when emitting ultrasonic waves or sound waves to the laminate (operation S40), the laminate may maintain a temperature of 25 to 100°C, and a pressure of 10 to 200 MPa may be applied to the laminate in a thickness direction of the laminate.

[0081] Figure 6 A flowchart schematically illustrating a method for manufacturing an all-solid-state battery according to another embodiment of the present invention is shown. Referring to this figure, the all-solid-state battery manufacturing method may further include, after emitting ultrasonic waves or sound waves to the laminate (operation S40), applying a pressure of 10 MPa to 200 MPa in a thickness direction of the laminate while maintaining a temperature of 25° C. to 100° C. (operation S50).

[0082] As described above, embodiments of the present invention relate to a method for manufacturing an all-solid-state battery, wherein ultrasonic waves or sound waves are emitted to form a uniform interface between lithium metal and a solid electrolyte layer, and the present invention will be described in more detail by the following examples. The following examples are only used to enhance the understanding of the present invention and are not intended to limit the scope of the present invention.

[0083] Example

[0084] (S10) A solid electrolyte layer including a sulfide-based solid electrolyte is prepared.

[0085] (S20) preparing a cathode including a cathode active material, a conductive material and a solid electrolyte, and placing the cathode on one surface of the solid electrolyte layer and pressurizing it.

[0086] (S30) A lithium foil is disposed on the other surface of the solid electrolyte layer, thereby producing a stacked product.

[0087] (S40) Figure 3 As shown, the laminate is inserted into a soft bag, and the ultrasonic generator is located outside the soft bag. The ultrasonic generator emits ultrasonic waves with a frequency of about 25kHz to the laminate for about 30 seconds, and then pauses the emission of ultrasonic waves for about 30 seconds. The emission of ultrasonic waves and the pause of the emission of ultrasonic waves are repeated 5 times, thereby completing the manufacture of the all-solid-state battery. During the emission of ultrasonic waves, the laminate is maintained at a temperature of about 100°C and pressurized at a pressure of about 20MPa.

[0088] Comparative Example 1

[0089] All-solid-state battery was manufactured by heating and pressing method. First, a laminate was obtained by the same method as in the above embodiment.

[0090] The stack was inserted into a soft-pack bag, and the all-solid-state battery was manufactured by heating the stack to a temperature of about 150° C. and pressurizing the stack at a pressure of about 200 MPa.

[0091] Comparative Example 2

[0092] An all-solid-state battery was prepared by the same method as in Comparative Example 1, except that the stack was heated to a temperature of about 150° C. and pressurized at a pressure of about 450 MPa.

[0093] Test Examples

[0094] The interface between the lithium metal and the solid electrolyte layer of the all-solid-state batteries according to Example, Comparative Example 1, and Comparative Example 2 was analyzed using a scanning electron microscope (SEM). Fig. 7A , 7B , 8A, 8B, 9A, and 9B describe the results of the analysis.

[0095] Fig. 7A is a photograph showing a scanning electron microscope (SEM) analysis result of a stack of an all-solid-state battery according to an embodiment, Figure 7B is a magnified photograph showing the interface between lithium metal and the solid electrolyte layer.

[0096] Fig. 8A is a photograph showing the SEM analysis result of the laminate of the all-solid-state battery according to Comparative Example 1, Figure 8B is a magnified photograph showing the interface between lithium metal and the solid electrolyte layer.

[0097] Fig.9A is a photograph showing the SEM analysis result of the laminate of the all-solid-state battery according to Comparative Example 2, Fig. 9B is a magnified photograph showing the interface between lithium metal and the solid electrolyte layer.

[0098] refer to Fig. 8A and 8B It can be confirmed that when an all-solid-state battery including an anode formed of lithium metal is manufactured by a heating and pressing method, an interface formed between the solid electrolyte layer 10 and the lithium metal 30 may be non-uniform.

[0099] refer to Fig.9A and 9B It can be confirmed that even if the pressure of the heating and pressurizing method is increased, the uneven bonding between the solid electrolyte layer 10 and the lithium metal 30 cannot be resolved. Moreover, when the pressure is excessively increased, the lithium metal 30 is melted and penetrated into the solid electrolyte layer 10, so that the anode is not formed. In this case, an electrical short circuit may occur and the all-solid-state battery cannot be operated.

[0100] refer to Fig. 7A and 7B, when the all-solid-state battery according to the embodiment of the present invention is manufactured by emitting ultrasonic waves or sound waves, a uniform interface may be formed between the solid electrolyte layer 10 and the lithium metal 30 .

[0101] As is apparent from the above description, in the method for manufacturing an all-solid-state battery according to an embodiment of the present invention, a uniform interface can be formed between the anode formed of lithium metal and the solid electrolyte layer. Therefore, the reduction in charging and discharging efficiency due to the non-uniformity of the anode thickness during charging and discharging can be prevented.

[0102] Moreover, using lithium metal as the anode can greatly increase the volume energy density and weight energy density of all-solid-state batteries.

[0103] Furthermore, the formation of dendrites during charge and discharge can be suppressed, so that the occurrence of a short circuit and a decrease in durability can be prevented.

[0104] Furthermore, large-area all-solid-state batteries with excellent quality can be manufactured at low cost in a short time.

[0105] The invention has been described in detail with reference to the embodiments. However, it will be appreciated by those skilled in the art that changes may be made in these embodiments without departing from the principles and spirit of the invention, the scope of which is defined in the appended claims and their equivalents.

Claims

1. A method for manufacturing an all-solid-state battery, the method comprising: preparing a solid electrolyte layer; placing lithium metal on a surface of the solid electrolyte layer to prepare a stack; as well as emitting ultrasonic or sonic waves to the stack, and The transmitting of ultrasonic waves or sound waves to the stack comprises: emitting ultrasonic or sonic waves to the stack for 10 to 30 seconds; and pausing the emission of the ultrasonic or sound waves to the laminate for 10 to 30 seconds, wherein the step of transmitting the ultrasonic wave or the sound wave to the laminate and pausing the transmission of the ultrasonic wave or the sound wave to the laminate is repeated 5 to 10 times, When emitting the ultrasonic wave or the sound wave to the laminate, the ultrasonic wave or the sound wave is emitted to the laminate while pressurizing the laminate in a thickness direction of the laminate at a pressure of 10 MPa to 200 MPa, and The stack is maintained at a temperature of 25°C to 100°C.

2. The method for manufacturing an all-solid-state battery according to claim 1, wherein: The solid electrolyte layer includes a sulfide-based solid electrolyte.

3. The method for manufacturing an all-solid-state battery according to claim 1, further comprising, before disposing the lithium metal, disposing a cathode on another surface of the solid electrolyte layer away from a surface on which the lithium metal is placed.

4. The method for manufacturing an all-solid-state battery according to claim 3, wherein: When the cathode is provided, the cathode and the solid electrolyte layer are stacked and then pressurized.

5. The method for manufacturing an all-solid-state battery according to claim 1, wherein: The lithium metal is lithium foil.

6. The method for manufacturing an all-solid-state battery according to claim 1, wherein: An ultrasonic generator or a sound wave generator is disposed outside the stack and emits ultrasonic waves or sound waves toward the stack.

7. The method for manufacturing an all-solid-state battery according to claim 6, wherein: The ultrasonic generator or sound wave generator is arranged on the whole or some areas of the outer surface of the laminate.

8. The method for manufacturing an all-solid-state battery according to claim 1, wherein: The stack is inserted into a soft bag and then ultrasonic or sonic waves are emitted to the stack.

9. The method for manufacturing an all-solid-state battery according to claim 8, wherein: The stack is inserted into a soft bag so that the entirety or certain areas of the outer surface of the stack are in contact with the inner surface of the soft bag.

10. The method for manufacturing an all-solid-state battery according to claim 8, wherein: An ultrasonic generator or a sound wave generator is disposed outside the soft-pack bag and emits ultrasonic waves or sound waves toward the stack.

11. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The ultrasonic generator or sound wave generator is arranged on the entire or certain areas of the outer surface of the soft bag.

12. The method for manufacturing an all-solid-state battery according to claim 1, wherein: When the ultrasonic wave or the sound wave is emitted to the stack, the ultrasonic wave or the sound wave has a frequency of 20 kHz to 40 kHz.

13. The method for manufacturing an all-solid-state battery according to claim 1, further comprising, after emitting ultrasonic waves or sound waves to the laminate, pressurizing the laminate in the thickness direction of the laminate at a pressure of 10 MPa to 200 MPa while maintaining the laminate at a temperature of 25°C to 100°C.

Citation Information

Patent Citations

  • Thin film type all-solid-state battery, and manufacturing method thereof

    KR101900823B1

  • Method for fabricating electrode

    JP2018170112A